2002
DOI: 10.1210/jcem.87.7.8682
|View full text |Cite
|
Sign up to set email alerts
|

Survivin Gene Expression in Endometriosis

Abstract: Survivin is a novel inhibitor of apoptosis and is expressed during fetal development and in cancer tissues, but its expression has not been reported in normal adult tissues or benign diseases. We investigated survivin gene and protein expression in a tumor-like benign disease, endometriosis, and correlated them with apoptosis and invasive phenotype of endometriotic tissues. Gene expression levels of survivin, matrix metalloproteinase (MMP)-2, MMP-9, and membrane type 1 (MT1)-MMP in 63 pigmented or nonpigmented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 40 publications
3
26
0
1
Order By: Relevance
“…Survivin, as a strong anti-apoptotic protein, has been demonstrated in fetal development, endometriosis and secretory phase of endometrium (Ambrosini et al 1997;Ueda et al 2002;Konno et al 2000). Whereas overexpression was found to be related with the aggressiveness of the tumor and resistance to chemotherapy and/or radiation (Zaffaroni et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Survivin, as a strong anti-apoptotic protein, has been demonstrated in fetal development, endometriosis and secretory phase of endometrium (Ambrosini et al 1997;Ueda et al 2002;Konno et al 2000). Whereas overexpression was found to be related with the aggressiveness of the tumor and resistance to chemotherapy and/or radiation (Zaffaroni et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, endometriotic lesions have also evolved strategies to evade apoptosis by: (i) increased Bcl-2, and decreased BAX (Meresman et al 2000); (ii) upregulation of survivin and matrix metalloproteinases (MMPs) (Ria et al 2002, Ueda et al 2002a; (iii) elevated soluble Fas ligand (FasL) and interleukin (IL)-8 in endometriotic peritoneal fluid (the increased FasL expression by IL-8 may induce apoptosis of T lymphocytes and thus enable endometriosis to evade immune-mediated cell death (Garcia-Velasco et al 2002)); and (iv) germline (Chang et al 2002) and somatically acquired (Bischoff et al 2002) inactivating mutations of p53 gene.…”
Section: Resistance To Apoptosismentioning
confidence: 99%
“…Thanks to these characteristics different from other proteins, it has attracted wide interest. Investigations of Ueda et al (2002) showed that the expression of survivin in ectopic lesions of the endometrium was higher than that in the normal one. They also found that the expression of survivin in pigmented lesions was higher than the non-pigmented lesions.…”
Section: Discussionmentioning
confidence: 99%